Detecting outstanding students for projection in academic competitions - Peinado Guevara, Hector J.; Peinado Guevara, Víctor Manuel; Sánchez Alcalde, Mary Cruz; González Félix, Griselda Karina; Sánchez Rodríguez , Claudia Eugenia; Moreno Lopez, Esteban Otoniel; Castro Rivera, Radames; Cuadras Berrelleza, Aldo Alan (Technium Social Sciences Journal, 2024)
Upper secondary educational institutions have outstanding students in different areas of knowledge. Some of them show scientific skills, technological innovation, and others are considered high-performance athletes. They can enhance their abilities and face more demanding challenges by participating in academic and/or sporting events. The aim of this study was "to discuss the importance of the timely detection of outstanding students in upper secondary education academic units, as well as to analyse the factors that influence the achievement of their goals". The research was conducted at the Guasave Daytime High School of the Autonomous University of Sinaloa (UAS), in the municipality of Guasave, Sinaloa, Mexico. It was designed as a case study, with an exploratory-explanatory analysis. A total of 455 surveys were administered to students. The academic unit has 3898 students, the data were captured in Google Forms to describe the attitudinal profile of high school students, ways of learning, strengths, and weaknesses to develop scientific skills. Interest in participating in important academic and sporting events was considered as activities to identify outstanding students. The results show the importance of implementing strategies that allow teachers to detect outstanding students in a timely manner. The dissemination of extracurricular activities was considered because students have the potential to develop their scientific and sporting talents. However, these activities have little dissemination among students. It is concluded that the Academic Units should have a greater dissemination of extracurricular activities and have a programme to detect outstanding students. It is important to train and guide teachers so that they can identify and channel outstanding students and be able to enhance their abilities.